The Spiderwick Chronicles: The Ironwood Tree - Book 4 - DiTerlizzi, Tony; Black, Holly (New York : Simon & Schuster Books for Young Readers, 2004)
After Mallory is kidnapped at her fencing meet, Jared and Simon search for her near an old quarry and find themselves amidst dwarves and goblins.
7 up.
Keywords: Dwarfs -- Fiction; Goblins -- Fiction; Brothers and sisters -- Fiction; Twins -- Fiction; Caves -- Fiction